2018
DOI: 10.1021/acsami.8b04708
|View full text |Cite
|
Sign up to set email alerts
|

Clickable-Zwitterionic Copolymer Capped-Quantum Dots for in Vivo Fluorescence Tumor Imaging

Abstract: In the last decades, fluorescent quantum dots (QDs) have appeared as high-performance biological fluorescent nanoprobes and have been explored for a variety of biomedical optical imaging applications. However, many central challenges still exist concerning the control of the surface chemistry to ensure high biocompatibility, low toxicity, antifouling, and specific active targeting properties. Regarding in vivo applications, circulation time and clearance of the nanoprobe are also key parameters to control the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 45 publications
1
43
1
Order By: Relevance
“…Another example is the work of Trapiella-Alfonso et al 29 In this study, the authors proposed nanoprobes based on QDs linked to peptides employing bioorthogonal coupling through the azide-alkyne click chemistry. After transferring hydrophobic ZnCuInSe/ZnS QDs to an aqueous medium using a two-step ligand exchange methodology the authors inserted azide functions at the QDs' surface by applying zwitterionic polymers.…”
Section: Click-chemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…Another example is the work of Trapiella-Alfonso et al 29 In this study, the authors proposed nanoprobes based on QDs linked to peptides employing bioorthogonal coupling through the azide-alkyne click chemistry. After transferring hydrophobic ZnCuInSe/ZnS QDs to an aqueous medium using a two-step ligand exchange methodology the authors inserted azide functions at the QDs' surface by applying zwitterionic polymers.…”
Section: Click-chemistrymentioning
confidence: 99%
“…For that, QDs have been conjugated with a variety of molecules, such as nucleic acids, 20 antibodies and/or their fragments, 21,22 lectins 23,24 and carbohydrates. 24,25 The QDs associated with specific molecules have been applied, as fluorescent nanotools, in a great variety of studies, such as quantitative and qualitative cell labeling, 22 receptor expression and recycling investigation, 26 yeast cells labeling, 23 parasite metabolism monitoring, 27 in vivo animal applications, 28,29 cancer diagnosis and therapy. 30 In addition, several studies have been developed in the field of fluoroimmunoassays and biosensors, 1,31,32 exploiting both optical and semiconductor properties of QDs.…”
Section: Introductionmentioning
confidence: 99%
“…Another advantage of QDs is the nanoscale dimensions, which makes QDs become appropriate labels for cellular analysis and imaging. The most common labeling method of cells by QDs is nonspecific (Ma et al, ; Pons et al, ; Trapiella‐Alfonso et al, ). Cao et al () demonstrated the internalization of C‐Dots in human breast cancer cells and used near‐infrared excitation to motivate the luminescence of C‐Dots to visualize the cells.…”
Section: Biomedical Applications Of Quantum Dotsmentioning
confidence: 99%
“…Application of colloidal semiconductor quantum dots (QDs) as luminescent markers in biotechnology relies on their narrow and controllable emission band, high photoluminescence (PL) quantum yield, possibility of excitation in a wide spectral range and excellent photostability. Nowadays, modern technology allows obtaining water‐soluble colloidal semiconductor QDs with a wide variety of functional groups on the surface . One of the most important steps for practical application of QDs is their controlled conjugation with various biomolecules .…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, modern technology allows obtaining water-soluble colloidal semiconductor QDs with a wide variety of functional groups on the surface. [1][2][3][4][5][6][7][8][9] One of the most important steps for practical application of QDs is their controlled conjugation with various biomolecules. [10][11][12][13] Unlike simple molecular systems, conjugation with colloidal nanoparticles possesses some specific features, which have to be taken into consideration when choosing conjugation methods.…”
Section: Introductionmentioning
confidence: 99%